2000
DOI: 10.1051/ocl.2000.0077
|View full text |Cite
|
Sign up to set email alerts
|

CORPS GRAS ET OBESITE Acides gras alimentaires et obésité : aspects qualitatifs et quantitatifs

Abstract: Résumé :Les triacylglycérols (TAG) adipocytaires représentent la principale forme de stockage des acides gras. Les TAG contiennent un mélange complexe d'acides gras qui diffèrent très nettement par leur structure moléculaire. En effet, les TAG adipocytaires contiennent un vaste spectre d'acides gras, allant en longueur de chaîne de 12 à 24 atomes de carbone et en insaturation de 0 à 6 doubles liaisons [1]. La nature des acides gras stockés dans le tissu adipeux dépend principalement de la composition en acides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Indeed several studies reported that the ω-3 fatty acids have an effect on gene expression and the liver. They are not only used as an energy source and as components of membrane phospholipids and also are important mediators of gene regulation (Raclot, 2000). There is an increase attention on impacts of preservation on nutritional qualities of dietary fish.…”
mentioning
confidence: 99%
“…Indeed several studies reported that the ω-3 fatty acids have an effect on gene expression and the liver. They are not only used as an energy source and as components of membrane phospholipids and also are important mediators of gene regulation (Raclot, 2000). There is an increase attention on impacts of preservation on nutritional qualities of dietary fish.…”
mentioning
confidence: 99%